2018
DOI: 10.1177/0309524x18780390
|View full text |Cite
|
Sign up to set email alerts
|

An extension of a strong viscous–inviscid coupling method for modeling the effects of vortex generators

Abstract: The aim of this work is to provide insights into the advantages and the limitations of the extension of a strong viscous-inviscid interactive code for modeling the effects of vortex generators, with focus on the calibration and validation for wind turbine airfoils. The proposed methodology relies on the approach proposed by other authors in the past and introduces an alternative formulation for the lag dissipation within the integral boundary-layer equations whose effects on the numerical prediction are evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…Kerho and Kramer 30 proposed introducing VG-added mixing into the boundary layer to the inviscid-viscous coupled code Xfoil through modifying the stress transport equation to mimic the behaviors of VGs. Daniele et al 31 suggested a sin-exponential increment instead of a step change in 30 , which was shown a good agreement with experimental results and increased numerical stability. De Tavernier 32 further extended Kerho and Kramer's approach 30 by introducing a smooth step function and decay rate to the source strength term to Xfoil 33 .…”
mentioning
confidence: 65%
“…Kerho and Kramer 30 proposed introducing VG-added mixing into the boundary layer to the inviscid-viscous coupled code Xfoil through modifying the stress transport equation to mimic the behaviors of VGs. Daniele et al 31 suggested a sin-exponential increment instead of a step change in 30 , which was shown a good agreement with experimental results and increased numerical stability. De Tavernier 32 further extended Kerho and Kramer's approach 30 by introducing a smooth step function and decay rate to the source strength term to Xfoil 33 .…”
mentioning
confidence: 65%
“…Kerho and Kramer 34 proposed introducing VG‐added mixing into the boundary layer to the inviscid‐viscous coupled code Xfoil through modifying the stress transport equation to mimic the behaviors of VGs. Daniele et al 35 suggested a sin‐exponential increment instead of a step change in Kerho and Kramer, 34 which was shown a good agreement with experimental results and increased numerical stability. De Tavernier et al 36 further extended Kerho and Kramer's approach 34 by introducing a smooth step function and decay rate to the source strength term to Xfoil 37 …”
Section: Introductionmentioning
confidence: 82%
“…As a rotating machine, the maximum Reynolds number of a wind turbine is proportional to the blade radius (it reaches up to Re = 25 × 10 6 in giant windmills) . In these cases, airfoils exhibit better performance, such as higher lift coefficient and lower drag ones, resulting in larger lift‐to‐drag ratio at a given angle of attack . However, to succeed in this performance improvement, one has to design VG's height according to the local boundary layer thickness.…”
Section: Discussionmentioning
confidence: 99%